(untitled) (Tanzania Journal for Population studies and Development, 2023)
A socio-ecological system is a multidimensional concept encompassing social relations and society-nature interactions. The concept has been used as a lens to assess various practices, particularly those related to environmental sustainability. However, the use of socio-ecological systems to assess sanitation practices in specific landscapes—such as gentle, sloping, and steep slopes where sanitation practices vary, affecting residents in multidimensional ways—remains unclear. This necessitated the use of socio-ecological systems by this study to examine the social relations and interaction between society and nature that influence sanitation practices. The study employed a cross-sectional explanatory survey design and involved a total of 288 residents who were randomly selected for primary data collection. The methods for data collection included household survey, review of written documents, key informant interviews and focus group discussions. The binary logistic regression was used to determine the association between advocacy and connection to water services, while content analysis was used to analyse qualitative data. Improved sanitation practices showed significant results with reporting inadequate sanitation to representatives, gentle slope and sloping landscape (p< 0.005). The construction of latrines was easier on gentle slopes compared to steep slopes. In a way socio-ecological systems affect communities’ efforts to access improved sanitation and their capacity to access better health services. Further progress could be achieved by improving relations among sanitation actors, empowering lower-income individuals to access planned areas for settlement development, and administering regulations for settlement development.